2020
DOI: 10.3390/nano10010121
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Cluster Analysis of Medical Chemicals Detected by a Bacteriophage-Based Colorimetric Sensor Array

Abstract: M13 bacteriophage-based colorimetric sensors, especially multi-array sensors, have been successfully demonstrated to be a powerful platform for detecting extremely small amounts of target molecules. Colorimetric sensors can be fabricated easily using self-assembly of genetically engineered M13 bacteriophage which incorporates peptide libraries on its surface. However, the ability to discriminate many types of target molecules is still required. In this work, we introduce a statistical method to efficiently ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 21 publications
0
28
0
Order By: Relevance
“…A self-assembling M13 bacteriophage structure was intensively investigated both in technical and medical applications, which was greatly reviewed by Moon et al [90]. Here, we would like to highlight sensing devices based on phage self-assembled structures that were examined to be potential diagnostics tools for varied (including medical) applications [91][92][93][94][95][96][97][98].…”
Section: Virus-based Colorimetric Sensorsmentioning
confidence: 99%
“…A self-assembling M13 bacteriophage structure was intensively investigated both in technical and medical applications, which was greatly reviewed by Moon et al [90]. Here, we would like to highlight sensing devices based on phage self-assembled structures that were examined to be potential diagnostics tools for varied (including medical) applications [91][92][93][94][95][96][97][98].…”
Section: Virus-based Colorimetric Sensorsmentioning
confidence: 99%
“…Some phages are also indicators of recreational water quality or even fecal indicators. Very recently, Kim et al [ 152 ] showed the utilization of bacteriophage-based colorimetric sensors for the detection of medical chemicals. Three variants of the M13 phage were used: wt , and two others that displayed specific peptides which changed the hydrophobic/hydrophilic balance of virions, respectively.…”
Section: Bacteriophages In Materials Sciencementioning
confidence: 99%
“…Another e-nose array of sensors experience has been designed to detect ammonia concentration in breath by means of a conductometric array of eleven different polyaniline nanocomposite sensors [3]; authors have chosen the sensor array approach due to the drift and sensitivity to humidity sensor weakness. An array of colorimetric sensors has been used for detecting extremely small amounts of target molecules [4], so that it analyzes a pattern of color change caused by a reaction between the sensor array and external substances. The biosensor array could detect hormone drugs (estrogen) and antibiotics.…”
Section: Introductionmentioning
confidence: 99%